NILAI PERUSAHAAN DI TENGAH ISU KEBERLANJUTAN: PERAN CORPORATE GOVERNANCE DALAM HUBUNGAN KINERJA LINGKUNGAN DAN KINERJA KEUANGAN - Yuliana Badren; Husin; Suhariyanto; Atika Purnamasari (Jurnal Widya Akuntansi dan Keuangan, 2026)
This research evaluates how environmental and financial outcomes dictate the market valuation of mining firms on the Indonesia Stock Exchange (2020-2024). Utilizing Moderated Regression Analysis (MRA) on a 17-company sample, the study examines the interaction between PROPER ratings, Return on Assets (ROA), and Tobin’s Q, with audit committee size serving as a moderator. The empirical results reveal that while profit-driven metrics (ROA) significantly boost firm value, ecological achievements (PROPER) fail to influence investor perception. Notably, corporate governance acts as a "double-edged" moderator: it intensifies the positive impact of financial health on valuation but diminishes the relevance of environmental performance. These insights suggest that Indonesian investors remain focused on bottom-line profitability. While robust governance enhances financial transparency, it has yet to successfully integrate sustainability as a strategic driver for shareholder wealth in the high-risk extractive industry.